Development of Nearpod Geometry Learning Media to Enhance Student’s Visual-Spatial Ability - Dewi Hamillah; Desy Lusiyana; Rifqi Hidayat (Pendidikan Matematika UNIMOR, 2025)
This research is motivated by the lack of relevant learning media for use in schools. The media currently used still includes worksheets, textbooks, and very limited visual aids. The purpose of this research is to develop Neargo (Nearpod Geometry) based learning media that is valid, practical, and effective in improving students' spatial visual abilities in seventh-grade geometry material. The method used is Research and Development (R&D) with the ADDIE model. The subjects of the research were students of class VII E at SMP Negeri 3 Sumber. Data collection techniques included test instruments and questionnaires, with both qualitative and quantitative data analysis. The results of validation by material experts showed a percentage of 86.67%, while validation by media experts obtained a percentage of 90.83%. The student response questionnaires showed an average of 97%, and the teacher response questionnaires showed a percentage of 95%, both in the very practical category. The average N-Gain result was 0.856, indicating a high improvement in the use of the developed learning media. Based on this analysis, it can be concluded that Neargo learning media is valid, practical, and effective in improving students' spatial visual abilities in geometry material in mathematics learning.